Material innovation preparation and performance study of semi-flexible pavement materials. (December 2022) - Zhang, Zhu; Li, Jiusu; Ni, Fujian
Abstract: Expounding the internal stability and rutting resistance of semi-flexible materials under different porosity can predict the relationship between pavement performance and material porosity. This study designed four porosities of 18%, 20%, 22%, and 25% to prepare the base asphalt mixture. Then the cement mortar was poured into the base asphalt mixture and cured for seven days under ambient temperature and humidity conditions to prepare semi-flexible pavement material. The stress-strain level of semi-flexible pavement(SFP) was analyzed by finite element software under the 20% porosity; the rutting test was used to evaluate the anti-rutting performance of SFP under different porosity. The orthogonal experiment indicated that the optimal ratio of cement mortar was 0.6 water-cement ratio, 15% mineral powder, and 35% sand. The finite element results further showed that the internal shear stress mainly causes the internal displacement and strain of the material. The shrinkage of the cement mortar was 0.168%, and the dynamic stability of SFP with porosity of 18%, 20%, 22%, and 25% were 6058, 7325, 11, 053, and 12, 353, respectively. The porosity and filling of cement mortar have a positive trend with the anti-rutting performance of semi-flexible pavement materials.